Regioselective synthesis and antimicrobial studies of novel bridgehead nitrogen heterocycles containing the thienopyrimidinone skeleton - Gaber, Hatem Moustafa; Moussa, Tarek Abdel-Mawgoud (European Journal of Chemistry, 2011)
Versatile 2-(alkylthio)pyrimidine-type and 2-(phenacylamino)thiophene building blocks (4a-d) and 16 were obtained based on an ortho functionalized thiophene derivative 1. A novel series of thieno[2,3-d]pyrimidin-4-one derivatives with annelated bridgehead nitrogen heterocycles was synthesized starting from precursors 4 and 16 through convenient methods. Cyclocondensation of 2-(phenacylthio)pyrimidinone derivative (4b) with sulfuric acid led to the tricyclic thiazole derivative 5. Initial hydrazinolysis of 3-(carbethoxymethyl)pyrimidinone derivative (4d) followed by nitrous acid deamination of the formed N-aminolactam (7) to obtain a N-protodeamino analogue 8a, which on further treatment with formaldehyde and piperidine yielded the respective Mannich-type base 8b. On the other hand, initial hydrazinolysis of 3-unsubstituted pyrimidinone derivative 4a and subsequent acetylation gave the condensed 3-methyltriazole derivative 12, whereas the condensed pyrrole derivative 19 was obtained by heterocyclization of 2-phenacylamine derivative 16 with malononitrile. All newly-obtained thienopyrimidinones with annelated bridgehead nitrogen were screened for their antimicrobial activity against strains of a representative panel of Gram-positive and Gram-negative bacteria as well as fungi together with reference drugs. The compounds under investigation displayed generally good in vitro antibacterial and antifungal activities, with compound 8b that has a N-piperidinylmethyl moiety showing essentially the highest inhibition in both assays. Despite promising antimicrobial activity of N-1-substituted imidazole derivative 8b, the corresponding N-1-unsubstituted analogue 8a displayed poor activity. The heteroannelation of a N-(piperidinylmethyl)imidazole or 3-methyltriazole moiety to the thienopyrimidinone scaffold could be considered as a potential strategy for the development of new therapeutic antimicrobial agents.